c-Jun N-Terminal Protein Kinase 1 (JNK1), but Not JNK2, Is Essential for Tumor Necrosis Factor Alpha-Induced c-Jun Kinase Activation and Apoptosis - Liu, Jing (American Society for Microbiology, 2004)
Two ubiquitously expressed isoforms of c-Jun N-terminal protein kinase (JNK), JNK1 and JNK2, have shared functions and different functions. However, the molecular mechanism is unknown. Here we report that JNK1, but not JNK2, is essential for tumor necrosis factor alpha (TNF-α)-induced c-Jun kinase activation, c-Jun expression, and apoptosis. Using mouse fibroblasts deficient in either Jnk1 or Jnk2, we found that JNK1 was activated by TNF-α, whereas JNK2 activation was negligible. In addition, JNK2 interfered with JNK1 activation via its “futile” phosphorylation by upstream kinases. Consequently, expression and activation of c-Jun, which depends on JNK activity, were impaired in Jnk1 null cells but enhanced in Jnk2 null cells. TNF-α-induced apoptosis was also suppressed in Jnk1 null fibroblasts but increased in Jnk2 null cells. Thus, our results provide a molecular mechanism underlying the different biological functions of JNK isoforms.